2-Aryl substituted pyridine C-region analogues of 2-(3-fluoro-4-methylsulfonylaminophenyl)propanamides as highly potent TRPV1 antagonists - Ryu, HyungChul (Bioorg Med Chem Lett, 2014)
A series of 2-aryl pyridine C-region derivatives of 2-(3-fluoro-4-methylsulfonylaminophenyl)propanamides were investigated as hTRPV1 antagonists. Multiple compounds showed highly potent TRPV1 antagonism toward capsaicin comparable to previous lead 7. Among them, compound 9 demonstrated anti-allodynia in a mouse neuropathic pain model and blocked capsaicin-induced hypothermia in a dose-dependent manner. Docking analysis of 9 with our hTRPV1 homology model provided insight into its specific binding mode.